A snapshot of the evolving epidemiology of oropharynx cancers. Issue 14 (30th April 2018) - Chaturvedi, Anil K.; Zumsteg, Zachary S.
Abstract : The trajectory of the human papillomavirus–positive oropharyngeal cancer epidemic in the United States reveals that "what's past is prologue" (William Shakespeare, The Tempest ): birth cohorts that previously experienced rises in incidence at younger ages do so now at older ages. Trials to determine the optimal clinical management of this increasingly older patient population are needed. See also pages 2993‐9.